Construção e validação de uma matriz de referência para o estudo das representações sociais sobre educação para a paz-tolerância - Santos, André Felipe Costa (2017)
In order to investigate Education for Peace, with emphasis on the principle of Tolerance, based on the theoretical-methodological contribution of Theory of Social Representations (MOSCOVICI, 1961/2012), influenced by studies in Educational Evaluation (STAKE, 1982), was elaborated and Validated a Reference Cadre in order to systematize and develop bases for empirical studies. For the elaboration of the Reference Cadre, was used a theoretical articulation with social representations (MOSCOVICI, 2012; JODELET, 2009), Research for Peace (GALTUNG, 1976), Education for Peace (JARES, 2002; GUIMARÃES , 2005), among other references (BOBBIO, 2004; FREIRE, 2005; WALZER, 1999). In order to achieve this, a first version of the Reference Cadre on Education for Peace-Tolerance was drawn up in three dimensions (Freedom of Thought and Expression, Social Rights, Political-Ideological) with five indicators each. For the validation of the Reference Cadre, its first version was submitted to the evaluation of a "prestige group" composed of university professors, who presented suggestions and recommendations with a view to improving the Reference Cadre. Incorporating the contributions and admonitions of the "prestige group" presented to the Reference Cadre, the Reference Cadre on Education for Peace-Tolerance had been re-elaborated and systematized with the help of the theoretical contribution of Theory of Social Representations (1961).At the same time, in order to provide a basis for future studies that can produce data collection tools from the Reference Cadre, using the method developed by Lahlou (2003) for the exploration of social representations in dictionaries, an exploratory survey of the entries Intolerance and Tolerance was made in five Portuguese language dictionaries. In order to aid in the analysis of the data produced, the software ALCESTE (Analyse Lexicale para Contexte d'Ensemble de Segment de Texte) version 2009 was used. Regarding the social representations of Intolerance registered in dictionaries, there are three categories (1 2. Intolerance Delimitation 2. Emotional Elements of Intolerance 3. Characteristics of Intolerant Subject); for Tolerance emerge two categories (1. Attributes of the Tolerant Subject 2. Actions Exerted by People / Institutions). In conclusion, the study produced: 1. A theoretical basis articulating studies of Education for Peace and Theory of Social Representations (1961); 2. A technical base, Reference Cadre on Education for Peace-Tolerance, which can be broadened and adapted to different subjects and social realities. 3. That there is in the social representation of Tolerance recorded in dictionaries a distinction between the tolerant subject and what is attributed as a tolerant person / institution, an illuminating aspect that should be considered in future studies